MA’NAVIYATNI IFODALOVCHI AYRIM TERMINLARNING LEKSIKOGRAFIK TALQINI - Sh.Norquziyev, J. (SCIENCE and SOCIETY, 2021)
The article provides a lexical interpretation of the main terms that make up the concept of spirituality, the transfer of the terms that form the spirituality of a person in the mind, the analysis of their meaning and interpretations, as well as suggestions and comments on improvement.
Keywords: spirituality; mother tongue; lexicography; conscience; faith; trust; intensely; sincerity; religions; duty